Impact of PNPLA3 rs738409 Polymorphism on the Development of Liver-Related Events in Patients With Nonalcoholic Fatty Liver Disease - Rosso, Chiara; Caviglia, Gian Paolo; Birolo, Giovanni; Armandi, Angelo; Pennisi, Grazia; Pelusi, Serena; Younes, Ramy; Liguori, Antonio; Perez-Diaz-del-Campo, Nuria; Nicolosi, Aurora; Govaere, Olivier; Castelnuovo, Gabriele; et al. (Clinical gastroenterology and hepatology, 2023)
Nonalcoholic fatty liver disease (NAFLD) is a complex disease, resulting from the interplay between environmental determinants and genetic variations. Single nucleotide polymorphism rs738409 C>G in the PNPLA3 gene is associated with hepatic fibrosis and with higher risk of developing hepatocellular carcinoma. Here, we analyzed a longitudinal cohort of biopsy-proven NAFLD subjects with the aim to identify individuals in whom genetics may have a stronger impact on disease progression. We retrospectively analyzed 756 consecutive, prospectively enrolled biopsy-proven NAFLD subjects from Italy, United Kingdom, and Spain who were followed for a median of 84 months (interquartile range, 65–109 months). We stratified the study cohort according to sex, body mass index (BMI) </≥30 kg/m2) and age (</≥50 years). Liver-related events (hepatic decompensation, hepatic encephalopathy, esophageal variceal bleeding, and hepatocellular carcinoma) were recorded during the follow-up and the log-rank test was used to compare groups. Overall, the median age was 48 years and most individuals were men (64.7%). The PNPLA3 rs738409 genotype was CC in 235 (31.1%), CG in 328 (43.4%), and GG in 193 (25.5%) patients. At univariate analysis, the PNPLA3 GG risk genotype was associated with female sex and inversely related to BMI (odds ratio, 1.6; 95% confidence interval, 1.1–2.2; P = .006; and odds ratio, 0.97; 95% confidence interval, 0.94–0.99; P = .043, respectively). Specifically, PNPLA3 GG risk homozygosis was more prevalent in female vs male individuals (31.5% vs 22.3%; P = .006) and in nonobese compared with obese NAFLD subjects (50.0% vs 44.2%; P = .011). Following stratification for age, sex, and BMI, we observed an increased incidence of liver-related events in the subgroup of nonobese women older than 50 years of age carrying the PNPLA3 GG risk genotype (log-rank test, P = .0047). Nonobese female patients with NAFLD 50 years of age and older, and carrying the PNPLA3 GG risk genotype, are at higher risk of developing liver-related events compared with those with the wild-type allele (CC/CG). This finding may have implications in clinical practice for risk stratification and personalized medicine. [Display omitted]